EVALUATING THE ROLE OF RELATIVE COMPETENCE IN LIMITING JUSTICE ACCESSIBILITY BEFORE ADMINISTRATIVE COURTS. - Fery Rochmad Ramadhan; Tunggul Anshari Setia Negara; Shinta Hadiyantina (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
The Administrative Court Procedure Law, as set out in Law Number 5 of 1986 and amended by Law Number 51 of 2009, aims to balance the inherently “unequal positions of claimants and government defendants”. Yet Indonesia’s extensive geography and shifting authority following the Job Creation Law have effectively centralized challenges to central government administrative decisions in Jakarta. Although the Administrative Court adheres to the actor sequitur forum rei principle, Article 54(4) provides for exceptions through a open legal policy by making “Peraturan Pemerintah” that has never been issued. This regulatory vacuum undermines access to justice, as claimants face strict filing deadlines, mandatory administrative effort, and significant geographical barriers. The absence of the mandated regulation reveals a broader disharmony in the legal framework and suggests governmental reluctance to establish venue rules that would facilitate citizen access to judicial review. Critical analysis with other jurisdictions demonstrates that relative competence rules can be structured to account for the nature of governmental acts, the extent of public harm, and the imperative of ensuring meaningful access to justice.